An updated Checklist of the Marine fishes from Syria with emphasis on alien species - ALI, MALEK FARES (Mediterranean Marine Science, 2018)
An updated checklist of marine ichthyofauna that are recorded to date, from Syrian marine water including 297 species (belonging to 220 genera, 111 families, 36 orders, and 3 classes) is presented. Sparidae is the dominant family (28 species), followed by Blenniidae (15 species), while 55 families are represented by 1 species. The Chondrichthyes present in Syria were cross-checked for the first time. The status, frequency, the main fishing gear targeting common species, in addition to the fishing method by which the rare species were caught, are also provided. Four species are recorded for the first time herein: Stomias boa boa (Risso, 1810), Hymenocephalus italicus Giglioli, 1884, Scarus ghobban Forsskal, 1775, and Nettastoma melanurum Rafinesque, 1810. In this inventory, 56 Lessepsian migrant species are also included, with 16 of them being considered as very common and of positive economic importance. Alien species have been grouped into three categories namely established (49 species), casual (2 species), and single records (5 species). Twenty-eight species were disregarded from this list, due to lack of solid documentation on their presence.